Family Resilience Index during the Covid 19 Pandemic in South Tangerang Society - Nufzatutsaniah, Nufzatutsaniah; Pratama , Yuga (ADPEBI, 2022)
Socio-psychological resilience is the main and substantial factor of South Tangerang families during the Covid 19 Pandemic. This study aims to analyze how high the level of family resilience in South Tangerang communities are; how is the relationship between variables and how is the relationship between indicators and their dimensions. It was found that the average value of the family resilience index of the South Tangerang community was 60.76. From the five dimensions, the highest index was the dimension of psychological social resilience which consisted of family harmony and legal compliance with the factor analysis method. This indicated that a family with good resilience was a family that did not occur violence against both spouses and children and did not violate the rules and laws. While the lowest index was the dimension of economic resilience, which meant that the COVID-19 pandemic had had a major impact on the ability of families to earn income.